The Digitalization of Islamic Education and Its Impact on Improving Students' Religious Literacy - Noprijon, Noprijon; Rasdiany, Apriana Nofriastuti; Zulfa, Mona Yulia; Sameto, Mayang Belia; Yusriandi, Yusriandi (Ahlussunnah: Journal of Islamic Education, 2024)
The digitalization of learning has become inevitable in the technological era, including in Islamic Religious Education (PAI) at Islamic universities. This study aims to analyze the impact of the digitalization of PAI learning on improving students' religious literacy. The approach used was descriptive qualitative, using interviews, observation, and documentation techniques with lecturers and students at private Islamic universities. The results show that the digitalization of learning contributes positively to improving students' cognitive, affective, and psychomotor aspects in understanding and practicing Islamic values. Students gain access to broader and more interactive materials, as well as flexible learning that adapts to their life contexts. This transformation also encourages changes in learning patterns, leading to more independent and reflective learning. PAI lecturers are also required to be able to adapt learning methods by utilizing digital technology creatively. However, several obstacles remain, such as limited devices, internet infrastructure, and low digital literacy among some students. Therefore, adaptive learning strategies, technology training for lecturers, and strengthening student learning motivation are needed so that the digitalization process truly supports the strengthening of religious literacy holistically and sustainably.